Ag-WC-C electric contact material and preparation method thereof

By combining the powder mixing and extrusion process, Ag-WC-C electrical contact materials with directional arrangement of carbon fibers were prepared, which solved the problems of poor mechanical fatigue resistance and insufficient density of existing materials, and achieved high conductivity, arc ablation resistance and long life.

CN119592886APending Publication Date: 2025-03-11WENZHOU HONGFENG ELECTRICAL ALLOY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411776315.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing Ag-WC-C electrical contact materials are prone to micro-cracking and cracking in high-dividing use cases, resulting in poor mechanical fatigue resistance, insufficient density, easy to consume contacts, and short life.

Method used

The combination of powder mixing and extrusion is adopted, and the mixed powder silver powder, tungsten carbide powder, carbon fiber powder and additive powder are formed through wet ball milling, drying, pre-firing, isostatic pressing, sintering, hot extrusion and heat treatment. The Ag-WC-C electrical contact material in a directional arrangement of carbon fibers is formed, and combined with a sterling silver belt through thermal composite.

Benefits of technology

The conductivity and density of Ag-WC-C electrical contact materials are improved, their mechanical fatigue resistance is enhanced, their electrical life is extended, and their arc ablation resistance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592886A_ABST
    Figure CN119592886A_ABST
Patent Text Reader

Abstract

The invention provides an Ag-WC-C electric contact material and a preparation method thereof, and the method comprises the steps: mixing silver powder, tungsten carbide powder, carbon fiber powder and additive powder according to a preset proportion to obtain mixed powder; carrying out wet ball milling on the mixed powder; carrying out drying treatment on the materials subjected to ball milling; pre-sintering the dried material; the pre-sintered material is subjected to isostatic pressing treatment, and an Ag-WC-C spindle is obtained; the Ag-WC-C ingot is sintered, and a green body is obtained; carrying out hot extrusion on the green body to obtain an Ag-WC-C strip; the Ag-WC-C strip is subjected to heat treatment; and thermally compounding the thermally treated Ag-WC-C strip with a pure silver strip to obtain the Ag-WC-C electric contact material. According to the invention, a powder mixing process and an extrusion process are combined, so that the conductivity, compactness, arc ablation resistance, mechanical fatigue resistance and the like of the Ag-WC-C electric contact material product are improved, and the service life of the Ag-WC-C electric contact material product is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electric contact materials, and in particular to an Ag-WC-C electric contact material and a preparation method thereof. Background Art

[0002] Ag-WC-C electrical contact material is widely used as contact material for electrical switches such as circuit breakers because of its good resistance to welding, electrical conductivity, thermal conductivity and arc erosion resistance.

[0003] At present, Ag-WC-C electrical contact materials are mainly prepared by powder pressing or chemical coating combined with powder pressing. The C particles in the Ag-WC-C material do not diffuse with Ag and WC. While the C particles improve the material's anti-adhesion and breaking performance, they also reduce its mechanical fatigue resistance. In some high-breaking applications of Ag-WC-C materials, stress is easily concentrated on the C particles of the Ag-WC-C material, resulting in microcracks and cracks in the Ag-WC-C contact material, thereby shortening the service life of electrical products such as circuit breakers.

[0004] Patent CN102051496A obtains Ag-WC-C electrical contact material with uniform dispersion through single powder processing, powder mixing, molding and sintering, but the material has poor density, easy consumption of contacts and easy cracking under high breaking force.

[0005] Patent CN103151186 improves the sintering characteristics of the material by mixing tungsten carbide powder with metal activator powder, graphite powder, and silver powder, and then performs ball milling, granulation, pressing, sintering, re-pressing and re-firing, and shaping. This improves the arc erosion resistance and electrical life of the material. However, it still has problems such as cracking, poor mechanical fatigue resistance, and easy agglomeration of WC at high breaking points.

[0006] Patent CN110373566B first obtains Ag-WC composite powder through ball milling, granulation, molding, degumming, infiltration, and crushing, and then mixes with Ag powder and graphite powder for a second time, and then sintering granulation, pressing molding, sintering, re-pressing, and heat treatment to obtain Ag-WC-C electrical contact material with a pebble-like structure. Although this patent solves the problem of WC reinforcing phase agglomeration, due to its Ag-WC composite powder, it still needs to be mixed with graphite powder for a second time. At high fracture, stress is still easily concentrated on the graphite particles, and its poor mechanical fatigue resistance has not been effectively solved.

[0007] Therefore, there is an urgent need for a highly conductive and long-life Ag-WC-C electrical contact material and a preparation method thereof, which can solve at least one of the problems of the existing Ag-WC-C electrical contact material, such as poor mechanical fatigue resistance, easy cracking at the C particles, uneven distribution, poor density, and easy contact consumption and short life, while maintaining the existing anti-welding performance. Summary of the invention

[0008] In view of the defects in the prior art, an object of the present invention is to provide an Ag-WC-C electrical contact material and a preparation method thereof.

[0009] According to one aspect of the present invention, there is provided a method for preparing an Ag-WC-C electrical contact material, comprising:

[0010] Mixing silver powder, tungsten carbide powder, carbon fiber powder and additive powder according to a preset ratio to obtain a mixed powder;

[0011] wet ball milling the mixed powder;

[0012] Drying the milled material;

[0013] Pre-burn the dried materials;

[0014] The pre-sintered material is subjected to isostatic pressing to obtain an Ag-WC-C ingot;

[0015] Sintering the Ag-WC-C ingot to obtain a green body;

[0016] hot extruding the green body to obtain a Ag-WC-C strip;

[0017] heat treating the Ag-WC-C strip;

[0018] The heat-treated Ag-WC-C strip is thermally composited with a pure silver strip to obtain an Ag-WC-C electrical contact material.

[0019] Optionally, the silver powder, tungsten carbide powder, carbon fiber powder and additive powder are mixed according to a preset ratio, wherein:

[0020] Tungsten carbide powder is 9.0-31.5 parts, carbon fiber powder is 0.5-5.5 parts, additive powder is 0.1-3.0 parts, and the balance is silver;

[0021] The components of the additive powder include any one or more of Zr, Cu, Ni, Zn, Cr, Fe, Ti, Mo, Co, rare earth elements, graphite, W metal and W metal compounds.

[0022] Optionally, the mixed powder is subjected to wet ball milling, wherein the ball-to-material ratio is 1 to 20, the rotation speed is 20 rpm to 200 rpm, and the ball milling time is 2 hours to 30 hours.

[0023] Optionally, the dried material is pre-burned, wherein: the pre-burning atmosphere is a reducing protective atmosphere, the pre-burning temperature is 250° C. to 650° C., and the time is 1 hour to 8 hours.

[0024] Optionally, the pre-burned material is subjected to isostatic pressing, wherein the pressure of the isostatic pressing is 10 MPa to 400 MPa and the time is 10 seconds to 120 seconds.

[0025] Optionally, sintering the Ag-WC-C ingot comprises:

[0026] First, the Ag-WC-C ingot is loaded into a sintering furnace and preheated in a reducing atmosphere at a temperature of 200° C. to 500° C. for a preheating time of 0.1 hour to 3 hours;

[0027] Then, the preheated Ag-WC-C ingot is subjected to a second-stage sintering in a reducing atmosphere, the sintering temperature is 350° C. to 650° C., and the sintering time is 0.5 hour to 5 hours;

[0028] The third stage sintering is then carried out in a reducing atmosphere at a sintering temperature of 650° C. to 920° C. for a sintering time of 0.5 to 10 hours, and then the product is cooled to room temperature and taken out of the furnace.

[0029] Optionally, the green body is hot extruded, wherein: the preheating temperature of the extrusion die is 300° C. to 500° C., the heating temperature of the hot extrusion is 650° C. to 900° C., the extrusion ratio is 10 to 200, and the extrusion time is 0.5 hour to 2 hours.

[0030] Optionally, the Ag-WC-C strip is subjected to heat treatment, wherein the heat treatment temperature is 350° C. to 600° C. and the time is 0.5 hour to 4 hours.

[0031] Optionally, the heat-treated Ag-WC-C strip is thermally composited with a pure silver strip, wherein: the thermal composite temperature is 680° C. to 900° C., and the thermal composite time is 0.25 hour to 4 hours.

[0032] According to another aspect of the present invention, there is provided an Ag-WC-C electrical contact material, which is prepared by the above-mentioned method for preparing the Ag-WC-C electrical contact material, and the Ag-WC-C electrical contact material has a microstructure with carbon fiber-like directional arrangement.

[0033] Compared with the prior art, the present invention has at least one of the following beneficial effects:

[0034] 1. The present invention adopts a combination of powder mixing and extrusion processes to make the carbon fibers evenly and directional distributed in the Ag-WC-C material, which is more conducive to the conduction of current, thereby greatly improving the conductivity of the Ag-WC-C electrical contact material product.

[0035] 2. The present invention can improve the material density through extrusion, so that the density of the Ag-WC-C electrical contact material far exceeds that of the conventional powder pressing method product. The Ag-WC-C material has lower resistivity and is more resistant to mechanical wear, thereby making the Ag-WC-C contact more resistant to arc erosion.

[0036] 3. The Ag-WC-C electrical contact material prepared by the present invention contains directional arranged carbon fibers as a reinforcing phase. The carbon fibers themselves are a high-strength, fatigue-resistant, and high-temperature-resistant fiber material. At the same time, the contact area between the carbon fibers and the matrix parallel to the force direction of the material is larger, thereby further improving the mechanical fatigue resistance of the material. In addition, the carbon fibers are dispersed and evenly distributed without aggregation, which is more conducive to material stress dispersion, thereby effectively solving the problems of low mechanical fatigue resistance and low service life in the existing preparation methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0038] Figure 1 Schematic diagram of the process of preparing Ag-WC-C electrical contact material in one embodiment of the present invention. DETAILED DESCRIPTION

[0039] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0040] Reference Figure 1 As shown, a method for preparing an Ag-WC-C electrical contact material provided by an embodiment of the present invention comprises the following steps:

[0041] S1, mixing silver powder, tungsten carbide powder, carbon fiber powder and additive powder according to a preset ratio to obtain a mixed powder;

[0042] S2, wet ball milling the mixed powder;

[0043] S3, drying the ball-milled material;

[0044] S4, pre-burning the dried material;

[0045] S5, subjecting the pre-sintered material to isostatic pressing to obtain an Ag-WC-C ingot;

[0046] S6, sintering the Ag-WC-C ingot to obtain a green body;

[0047] S7, hot extruding the green body to obtain an Ag-WC-C strip;

[0048] S8, heat treating the Ag-WC-C strip;

[0049] S9. The heat-treated Ag-WC-C strip is thermally composited with a pure silver strip, and the pure silver strip is used as a silver coating layer and composited on the bottom of the Ag-WC-C strip to obtain an Ag-WC-C electrical contact material with directional arrangement of carbon fibers.

[0050] In some embodiments, in step S1, silver powder, tungsten carbide powder, carbon fiber powder, and additive powder are placed in a powder mixer according to a preset ratio for mixing, and the mixing time is 1 hour to 30 hours. Among them, the weight proportions of various powders are: tungsten carbide powder is 9.0 to 31.5 parts, carbon fiber powder is 0.5 to 5.5 parts, additive powder is 0.1 to 3.0 parts, and the balance is silver. Carbon fiber powder, as a reinforcing phase, can increase the resistance to fusion welding of the electrical contact material, and its lubricating properties help reduce the surface contact resistance of the electrical contact and improve the electrical conductivity of the electrical contact. The components of the additive powder include any one or more of Zr, Cu, Ni, Zn, Cr, Fe, Ti, Mo, Co, rare earth elements, graphite, W metal and W metal compounds. The role of the additive powder is to improve the interface wettability of the reinforcing phase (WC, C) and the matrix (Ag), improve the bonding strength of WC and the silver matrix, improve the plasticity of the material, and regulate the comprehensive electrical properties of the material. Through the powder mixing steps and parameter settings, the dispersion of the powder is improved to ensure that the powders are mixed evenly.

[0051] In some embodiments, in step S2, the mixed powder and the liquid medium are placed in a horizontal ball mill for wet ball milling, wherein the ball-to-material ratio is 1 to 20, the rotation speed is 20 rpm to 200 rpm, and the ball milling time is 2 hours to 30 hours, so as to increase the surface activity of the powder, thereby increasing the bonding strength between the reinforcing phase and the silver matrix.

[0052] In some embodiments, in step S3, the ball-milled material is placed in an oven, inert gas is introduced for protection, and then dried at a temperature of 50° C. to 150° C. for 2 hours to 20 hours to remove the liquid medium in the ball-milled powder.

[0053] In some embodiments, in step S4, the dried material is placed in a heat treatment furnace for pre-calcination, the pre-calcination atmosphere is a reducing protective atmosphere, the pre-calcination temperature is 250°C to 650°C, and the time is 1 hour to 8 hours, thereby changing the physical and chemical properties of the powder and preparing for the densification of the powder in the subsequent process. Then, the powder is crushed and sieved to screen out the powder of suitable particle size, and the sieve aperture of the sieve is 100 mesh to 400 mesh.

[0054] In some embodiments, in step S5, the isostatic pressing treatment is performed at a pressure of 10 MPa to 400 MPa for a time of 10 seconds to 120 seconds to form a dense ingot without chipping.

[0055] In some embodiments, sintering an Ag—WC—C ingot includes:

[0056] S61, firstly loading the Ag-WC-C ingot into the sintering furnace, and then preheating it in a reducing atmosphere, the preheating temperature is 200° C. to 500° C., and the preheating time is 0.1 hour to 3 hours; through the first stage sintering, a part of the pores in the particles and the ingot are removed;

[0057] S62, then performing a second-stage sintering on the preheated Ag-WC-C ingot in a reducing atmosphere, the sintering temperature is 350° C. to 650° C., and the sintering time is 0.5 hour to 5 hours; through the second-stage sintering, a neck connection is formed between the powders;

[0058] S63, then carry out the third stage sintering in a reducing atmosphere, the sintering temperature is 650℃~920℃, the sintering time is 0.5 hour~10 hours, and then cool to room temperature and take out of the furnace. Through the third stage sintering, the pores are reduced and shrunk, the lattice distortion is reduced, and the density and conductivity of the material are improved.

[0059] Preferably, H2 or a nitrogen-hydrogen mixed gas is used as the reducing atmosphere.

[0060] Through the above sintering steps and sintering parameter settings, a neck-shaped connection is formed between the powders, the pores are reduced and shrunk, and the densification of the material is further improved.

[0061] In some embodiments, in step S7, the sintered green body is placed in an extruder and hot extruded into a strip under a protective atmosphere, wherein: the preheating temperature of the extrusion die is 300°C to 500°C, the heating temperature of the hot extrusion is 650°C to 900°C, the extrusion ratio is 10 to 200, and the extrusion time is 0.5 hours to 2 hours. Extrusion is equivalent to pressurizing the material from multiple directions, so that the material density far exceeds the conventional powder pressing method product, and extrusion makes the reinforcing phase carbon fiber oriented in the silver matrix, and the lubricating properties of the carbon fiber make the contact material surface contact resistance lower and more resistant to arc ablation.

[0062] In some embodiments, in step S8, the extruded Ag-WC-C strip is placed in a heat treatment furnace, N2 is introduced, and heat treatment is performed; wherein: the heat treatment temperature is 350°C to 600°C, and the time is 0.5 hour to 4 hours.

[0063] In some embodiments, in step S9, the interface surface of the Ag-WC-C strip and the pure silver strip to be composited is first treated, and then placed in a device with a protective gas for thermal composite, and then the composite strip is cold rolled to a desired thickness, wherein: the thermal composite temperature is 680°C to 900°C, and the thermal composite time is 0.25 hour to 4 hours.

[0064] Another embodiment of the present invention provides an Ag-WC-C electrical contact material, which is prepared using the above-mentioned method for preparing the Ag-WC-C electrical contact material. The Ag-WC-C electrical contact material has a microstructure with carbon fiber-like directional arrangement, and the material density far exceeds that of conventional powder pressing products. The lubricating properties of carbon fibers make the contact material surface contact resistance lower, which also makes the Ag-WC-C material have lower resistivity and is more resistant to arc erosion. The Ag-WC-C electrical contact product made of this material has high conductivity and longer electrical life.

[0065] In the above embodiments, the directional carbon fiber has the advantages of lubricity, resistance to welding, high strength, and mechanical fatigue resistance. If the carbon fiber is used alone as a reinforcing phase, it is not resistant to high current ablation, wear resistance, and the life is not long; WC particles have the characteristics of high melting point, arc ablation resistance, but not resistance to welding. If WC is used alone as a reinforcing phase, WC particles are prone to aggregation, resulting in problems such as material hole defects and high resistivity; the combination of carbon fiber and WC particles is conducive to providing electrical contact materials with high current ablation resistance, wear resistance, and electrical life. The powder mixing method improves the situation of WC aggregation leading to hole defects, while the extrusion method makes the C fibers arranged in a directional manner, improves the material's density and mechanical fatigue resistance, and improves the material's conductivity. The AgWCC material prepared by the powder mixing method and the extrusion method makes up for their respective defects, so that the material has good resistance to welding, high density, and mechanical fatigue resistance, and also has the characteristics of arc ablation resistance, high electrical life, and lower resistivity. In the above embodiment of the present invention, according to the application of high-breaking of circuit breakers, the two processes of powder mixing and extrusion are combined, and the different organizational structure characteristics of the materials are comprehensively considered, such as high-strength and fatigue-resistant carbon fiber, high density, arc erosion resistance, welding resistance and other key parameters, and optimized combination is performed to form a complementary and synergistic enhancement effect within the material through key performance parameters, thereby improving the overall performance of the material. The method in the above embodiment of the present invention is easy to operate, low in cost, has no special requirements for equipment, and the prepared electrical contact material has a high breaking capacity and a long service life for switch electrical appliances.

[0066] Continue to refer to Figure 1 In a specific embodiment, a method for preparing a high-conductivity and long-life AgWC12C3 electrical contact material comprises the following steps:

[0067] S1: silver powder, tungsten carbide powder, carbon fiber powder and additive powder are placed in a powder mixer according to a preset ratio and mixed for 2 hours; wherein the additive powder refers to Mo metal and graphite, and the weight proportions of various powders are: tungsten carbide is 14 parts, carbon fiber is 3.5 parts, additive powder is 0.5 parts, and the remainder is silver, to obtain a mixed powder.

[0068] S2: The sieved mixed powder and acetone are placed in a horizontal ball mill for wet ball milling, wherein the ball milling process parameters are: ball-to-material ratio of 8, rotation speed of 150 rpm, and ball milling time of 6 hours.

[0069] S3: The ball-milled material is placed in an oven, and argon inert gas is introduced for protection, and then dried; the drying temperature is 80° C. and the time is 4 hours.

[0070] S4: placing the dried material in a heat treatment furnace for pre-burning, and then crushing and screening; wherein the pre-burning temperature is 500°C, the pre-burning atmosphere is H2 atmosphere, the time is 4 hours, and the sieve aperture is 300 mesh.

[0071] S5: isostatically pressing the pre-sintered powder at a pressure of 400 MPa for 100 seconds to obtain an Ag-WC-C ingot.

[0072] S6: After the Ag-WC-C ingot is loaded into the sintering furnace, it is preheated in a nitrogen-hydrogen mixed gas atmosphere at a temperature of 350°C for 1.5 hours; then the preheated ingot is sintered in a second stage in a H2 atmosphere at a temperature of 650°C for 3 hours; then the third stage is sintered in a H2 atmosphere at a temperature of 870°C for 6 hours, and then cooled to room temperature and taken out of the furnace to obtain a green body;

[0073] S7: placing the sintered green body in a 1000T extruder, and hot extruding it into a Ag-WC-C strip under a N2 protective atmosphere; wherein the heating temperature of the hot extrusion is 850°C, the extrusion ratio is 120, the extrusion time is 1 hour; and the preheating temperature of the extrusion die is 350°C.

[0074] S8: placing the extruded Ag-WC-C strip in a heat treatment furnace, introducing N2, and performing heat treatment; the heat treatment temperature is 500°C and the time is 2 hours.

[0075] S9: First, treat the interface surface of the heat-treated Ag-WC-C strip and the pure silver strip to be composited, and then place them in a device with N2 protective gas for thermal composite. The thermal composite temperature is 780°C and the thermal composite time is 0.5 hour. Then, cold roll the composite strip to the required thickness to obtain AgWC12C3 electrical contact material with directional arrangement of carbon fibers (the numbers represent the corresponding percentage content).

[0076] AgWC12C3 prepared by powder pressing method is used as a comparison. The test results of the flexural strength and electrical life test performance of the two are shown in Table 1.

[0077] Table 1 Test results of bending strength and electrical life test performance

[0078] Bending strength Electrical life test Pressed powder method AgWC12C3 180MPa 9000 times This application AgWC12C3 310MPa 15000 times

[0079] According to the performance test results in Table 1, compared with the powder pressing method, the Ag-WC-C material prepared by the method in the above embodiment of the present invention has higher bending strength and longer electrical life (i.e., service life).

[0080] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various modifications or variations within the scope of the claims, which does not affect the essence of the present invention. The above preferred features can be used in any combination without conflicting with each other.

Claims

1. A method for preparing an Ag-WC-C electrical contact material, characterized in that: include: Mixing silver powder, tungsten carbide powder, carbon fiber powder and additive powder according to a preset ratio to obtain a mixed powder; wet ball milling the mixed powder; Drying the milled material; Pre-burn the dried materials; The pre-sintered material is subjected to isostatic pressing to obtain an Ag-WC-C ingot; Sintering the Ag-WC-C ingot to obtain a green body; hot extruding the green body to obtain a Ag-WC-C strip; heat treating the Ag-WC-C strip; The heat-treated Ag-WC-C strip is thermally composited with a pure silver strip to obtain an Ag-WC-C electrical contact material.

2. The method for preparing the Ag-WC-C electrical contact material according to claim 1, characterized in that: The silver powder, tungsten carbide powder, carbon fiber powder and additive powder are mixed according to a preset ratio, wherein: Tungsten carbide powder is 9.0-31.5 parts, carbon fiber powder is 0.5-5.5 parts, additive powder is 0.1-3.0 parts, and the balance is silver; The components of the additive powder include any one or more of Zr, Cu, Ni, Zn, Cr, Fe, Ti, Mo, Co, rare earth elements, graphite, W metal and W metal compounds.

3. The method for preparing the Ag-WC-C electrical contact material according to claim 1, characterized in that: The mixed powder is subjected to wet ball milling, wherein the ball-to-material ratio is 1-20, the rotation speed is 20 rpm-200 rpm, and the ball milling time is 2 hours-30 hours.

4. The method for preparing the Ag-WC-C electrical contact material according to claim 1, characterized in that: The dried material is pre-burned, wherein: the pre-burning atmosphere is a reducing protective atmosphere, the pre-burning temperature is 250° C. to 650° C., and the time is 1 hour to 8 hours.

5. The method for preparing the Ag-WC-C electrical contact material according to claim 1, characterized in that: The pre-burned material is subjected to isostatic pressing, wherein the pressure of the isostatic pressing is 10 MPa to 400 MPa and the time is 10 seconds to 120 seconds.

6. The method for preparing the Ag-WC-C electrical contact material according to claim 1, characterized in that: Sintering the Ag-WC-C ingot, comprising: First, the Ag-WC-C ingot is loaded into a sintering furnace and preheated in a reducing atmosphere at a temperature of 200° C. to 500° C. for a preheating time of 0.1 hour to 3 hours; Then, the preheated Ag-WC-C ingot is subjected to a second-stage sintering in a reducing atmosphere, the sintering temperature is 350° C. to 650° C., and the sintering time is 0.5 hour to 5 hours; The third stage sintering is then carried out in a reducing atmosphere at a sintering temperature of 650° C. to 920° C. for a sintering time of 0.5 to 10 hours, and then the product is cooled to room temperature and taken out of the furnace.

7. The method for preparing the Ag-WC-C electrical contact material according to claim 1, characterized in that: The hot extrusion of the green body comprises: the preheating temperature of the extrusion die is 300° C. to 500° C., the heating temperature of the hot extrusion is 650° C. to 900° C., the extrusion ratio is 10 to 200, and the extrusion time is 0.5 hour to 2 hours.

8. The method for preparing the Ag-WC-C electrical contact material according to claim 1, characterized in that: The Ag-WC-C strip is subjected to heat treatment, wherein the heat treatment temperature is 350° C. to 600° C. and the time is 0.5 hour to 4 hours.

9. The method for preparing the Ag-WC-C electrical contact material according to claim 1, characterized in that: The heat-treated Ag-WC-C strip is thermally composited with a pure silver strip, wherein the thermal composite temperature is 680° C. to 900° C. and the thermal composite time is 0.25 hour to 4 hours.

10. An Ag-WC-C electrical contact material, characterized in that: The Ag-WC-C electrical contact material is prepared by the preparation method of the Ag-WC-C electrical contact material according to any one of claims 1 to 9, wherein the Ag-WC-C electrical contact material has a microstructure with carbon fiber-like directional arrangement.

Citation Information

Patent Citations

  • Electric contact material made of silver-tungsten carbide graphite and preparation method thereof

    CN102051496A

  • A special AgWCC electrical contact material with a unique microstructure and its preparation method

    CN110373566B